Notices (Blackfriars, 1935)
Vocation to Marriage. By Fr. Bede Jarrett, O.P. Holy Week. By Fr. Bede Jarrett, O.P. Erasme. By Th. Quoniam. Henrici Sexti Angliae Regis Miracula Postuma. Ed. by P. Grosjean, S.J. The Akathistos Hymn. Translated by Fr. Vincent McNabb, O.P., S.T.M. Early Irish, Laws and Institutions. By Eoit MacNeill. Mary Stuart, Forgotten Forgeries. By Sir George Turner. Ideal Motherhood. By Mary Kidd, M.B. Lond. Foreword by Dame Louise Mcllroy, M.D., D.Sc. La Vie est-elle une Fete? Chanoine J. Choquet. Catherine Fougere. By Jacqueline Vincent.